2015
DOI: 10.4103/1947-2714.170621
|View full text |Cite
|
Sign up to set email alerts
|

The need to emphasize nephrology knowledge in residents-in-training

Abstract: Background:Chronic kidney disease is an increasingly prevalent health problem with the potential for poor outcome of end-stage renal disease. Hospitalized critically ill patients are prone to acute renal injury from numerous factors such as poor renal perfusion secondary to ischemia and hypotension, nephrotoxin exposure, and intravenous contrast exposure.Aims:We set to explore resident awareness and knowledge about chronic kidney disease management, timely nephrology referrals, preventing inadvertent acute kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…An elective in a subspecialty helps internal medicine trainees improve their understanding in areas which may translate to their clinical practice (Akbar et al 2015, Shah et al 2015. Goldenberg et al (1983) were able to demonstrate this educational impact in a group of residents undergoing a rheumatology elective.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An elective in a subspecialty helps internal medicine trainees improve their understanding in areas which may translate to their clinical practice (Akbar et al 2015, Shah et al 2015. Goldenberg et al (1983) were able to demonstrate this educational impact in a group of residents undergoing a rheumatology elective.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the increasing burden of CKD, there is a declining interest in nephrology fellowships (Sharif et al 2016, Field 2008, Jhaveri et al 2013. The various reasons given include poor learning experiences with nephrology in medical school, nephrology not being a core rotation, the perception that work hours are very long, and exposure to very sick patients such as dialysis or transplant patients in a hospital setting (Jhaveri et al 2013, Akbar et al 2015, Shah et al 2015. As patients with acute kidney injury (AKI), CKD and fluid electrolyte imbalance are routinely admitted to medical wards, not only specialist nephrologists but also internal medicine (IM) physicians will need to be conversant in their management.…”
Section: Introductionmentioning
confidence: 99%
“…For example, significant knowledge gaps regarding management of chronic kidney disease were identified in a survey of internal medicine, internal medicine/ pediatrics, and family medicine residents. (11) Similarly, internal medicine house-staff had poor awareness and knowledge for dose adjustment for common cardiovascular drugs in patients with chronic kidney disease, (12) and specific gaps in knowledge of chronic kidney disease guidelines. (13) Finally, a study investigating knowledge about menopause management among all levels of internal medicine, family medicine, and obstetrics and gynecology residents showed that despite the belief that training in menopause management was important, knowledge gaps were present, and a minority felt adequately prepared to manage women experiencing menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Having additional nephrology education either in medical school or in residency is associated with improved level of awareness and knowledge among IMHS. [ 18 ] Both internal medicine residents and PCPs have gaps in their knowledge of CKD practice guidelines and treatment of CKD complications. [ 19 ] Improved education of CKD among training physicians can result in improved patient care and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Improved education of CKD among training physicians can result in improved patient care and clinical outcomes. [ 18 ] This may come in the form of additional ambulatory Nephrology exposure as conditions such as CKD are best taught in the outpatient setting. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%